The use of the computer in decentralised collective bargaining in South Africa with special reference to the development of a computer-assisted costing model - Brand, Abraham Marthinus (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 1992.